TRANSFORMASI GERAKAN TAJDID DI ERA DISRUPSI: ANALISIS FILOSOFIS DAN STRATEGIS MUHAMMADIYAH MENUJU ISLAM BERKEMAJUAN - Riska Putri Rusnadi; Sitti Aisyiah; Dahlan Lama Bawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is based on the importance of transforming the tajdid movement as a key determinant of the success of Islamic da'wah in the era of disruption, which often faces challenges in the relevance of strategies and adaptation of information technology. This research aims to conduct a comprehensive analysis of the historical roots, the vision of "A True Islamic Society," the mission of enlightenment, and the strategic role of the autonomous Muhammadiyah organization in responding to contemporary dynamics. The method used is descriptive qualitative through library research. Data collection techniques include reviewing official organizational documents, congress manuscripts, and scientific journal articles related to Muhammadiyah's development. The results show that the management practices of the Muhammadiyah movement have been running very well, where the vision of Progressive Islam is implemented transparently through strengthening Muhammadiyah's Amal Usaha (AUM) and reflective-dialogical digital da'wah. This finding implies that the integration of the purification of faith and the dynamism of muamalah through institutional innovation is key to organizational sustainability. The novelty of this research lies in the analytical model of Muhammadiyah's da'wah strategy, which integrates aspects of critical digital literacy and strengthening economic independence as organizational culture in the cyber era. This research contributes to providing a best practice model for the governance of modern, inclusive and progressive religious organizations at the national and international levels.